Adsorption of benzoxaboroles on hydroxyapatite phases. (1st September 2016) - Pizzoccaro, Marie-Alix; Nikel, Ondrej; Sene, Saad; Philippe, Coralie; Mutin, P. Hubert; Bégu, Sylvie; Vashishth, Deepak; Laurencin, Danielle
Graphical abstract: Abstract: Benzoxaboroles are a family of molecules that are finding an increasing number of applications in the biomedical field, particularly as a "privileged scaffold" for the design of new drugs. Here, for the first time, we determine the interaction of these molecules with hydroxyapatites, in view of establishing (i) how benzoxaborole drugs may adsorb onto biological apatites, as this could impact on their bioavailability, and (ii) how apatite-based materials can be used for their formulation. Studies on the adsorption of the benzoxaborole motif (C7 H7 BO2, referred to as BBzx) on two different apatite phases were thus performed, using a ceramic hydroxyapatite (HAceram ) and a nanocrystalline hydroxyapatite (HAnano ), the latter having a structure and composition more similar to the one found in bone mineral. In both cases, the grafting kinetics and mechanism were studied, and demonstration of the surface attachment of the benzoxaborole under the form of a tetrahedral benzoxaborolate anion was established using 11 B solid state NMR (including 11 B- 31 P correlation experiments). Irrespective of the apatite used, the grafting density of the benzoxaborolates was found to be low, and more generally, these anions demonstrated a poor affinity for apatite surfaces, notably in comparison with other anions commonly found in biological media, such as carboxylates and (organo)phosphates. The study was then extended to the adsorption of a molecule with antimicrobial and antifungal properties (3-piperazine-bis(benzoxaborole)), showing, on a more general perspective, how hydroxyapatites can be used for the development of novel formulations of benzoxaborole drugs. Statement of Significance: Benzoxaboroles are an emerging family of molecules which have attracted much attention in the biomedical field, notably for the design of new drugs. However, the way in which these molecules, once introduced in the body, may interact with bone mineral is still unknown, and the possibility of associating benzoxaboroles to calcium phosphates for drug-formulation purposes has not been looked into. Here, we describe the first study of the adsorption of benzoxaboroles on hydroxyapatite, which is the main mineral phase present in bone. We describe the mode of grafting of benzoxaboroles on this material, and show that they only weakly bind to its surface, especially in comparison to other ionic species commonly found in physiological media, such as phosphates and carboxylates. This demonstrates that administered benzoxaborole drugs are unlikely to remain adsorbed on hydroxyapatite surfaces for long periods of time, which means that their biodistribution will not be affected by such phenomena. Moreover, this work shows that the formulation of benzoxaborole drugs by association to calcium phosphates like hydroxyapatite will lead to a rapid release of the molecules.